Implementation of the european green strategy. Synergy of educational, scientific, managerial and industrial components for climate management and climate change prevention / Climan Erasmus+ KA2 - Liuta, Oksana; Malovanyy, Myroslav; Vnukova, Nataliia; Tymchuk, Ivan; Zhelnovach, Ganna; Kordzadze, Tea (Видавництво Львівської політехніки, 2023)
The urgent problems related to environmental and climate factors, the solution of which requires the involvement of highly qualified and narrow-profile specialists capable of solving and developing effective measures to minimize the negative effects of global warming, were analyzed. The analysis demonstrates that today in Ukraine, there is an urgent need to train climate management specialists due to the global nature of this problem. The main aspects and advantages of the participation of Ukrainian universities in the joint project Erasmus+ KA2 “Synergy of educational, scientific, managerial and industrial components for climate management and climate change prevention” (Climan), which promotes the implementation of multi-level education and professional training on climate services, climate change adaptation and mitigation at the local, national and regional levels are presented. The important particularities and innovative results of the project implementation in higher education institutions in Ukraine, which involve creating climate management centres based on educational institutions, developing interdisciplinary training modules Climate Management, and training qualified climate managers, were described.
Keywords: education; Climan project; climate change; adaptation; mitigation